Efficacy of the hepatitis B vaccine alone in the prevention of hepatitis B perinatal transmission in infants born to hepatitis B e antigen-negative carrier mothers - Wenjun Zhang; Chenyu Xu; Yanjing Rui; Jie Chen; Tingmei Chen; Yimin Dai; Biyun Xu; Yali Hu; Junhao Chen; Yi-Hua Zhou (Journal of Virus Eradication, 2022)
Background: Vertical mother-to-child transmission (MTCT) of the hepatitis B virus (HBV) remains an important issue. Timely administration of hepatitis B immunoglobulin (HBIG) and of the HBV vaccine is effective in preventing MTCT in infants born to HBV-infected mothers. However, HBIG is often not easily available in low-income countries or regions. Methods: We compared in a retrospective cohort study the HBV vaccine efficacy alone and in combination with HBIG in preventing vertical MTCT in infants born to HBeAg-negative carrier mothers in Jiangsu province, China. Based on the administration of the HBV vaccine and HBIG shortly after birth, children were divided into two groups: Group 1, administration of the HBV vaccine alone, and Group 2, concurrent use of HBIG and of the HBV vaccine. Results: A total of 620 infants born to HBeAg-negative carrier mothers were enrolled into this study. Group 1 included 195 children who had received the HBV vaccine alone after birth, and Group 2, 425 children who had received both HBIG and the HBV vaccine. Children were followed up to the age of 68 and 42 months, respectively. MTCT of HBV occurred in 0% (0/195) in Group 1 (HBV vaccine alone) and 0% (0/425) in Group 2 (HBV vaccine and HBIG) (p = 1.00). Conclusion: In this retrospective cohort study, we found that HBV vaccination alone shortly after birth was effective in preventing MTCT of HBV in infants born to HBeAg-negative carrier mothers.